2011
DOI: 10.1097/fjc.0b013e31821e5626
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 (CD26) Inhibitor Alogliptin Inhibits Atherosclerosis in Diabetic Apolipoprotein E–Deficient Mice

Abstract: Dipeptidyl peptidase-4 (DPP-4 or CD26) inhibitors, a new class of anti-diabetic compounds, are effective in treatment of hyperglycemia. Since atherosclerosis-related cardiovascular diseases are the major complications of diabetes, it is important to determine the effect of DPP-4 inhibitors on atherosclerosis. In this study, nondiabetic and diabetic apolipoprotein E (apoE)-deficient mice were treated with DPP-4 inhibitor alogliptin for 24 weeks and atherosclerotic lesions in aortic origins were examined. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
103
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 42 publications
5
103
0
Order By: Relevance
“…To obtain further insight into the role of incretins in the effects of DPP- activity. It has also been reported that a DPP-4I inhibited toll-like receptor 4-mediated extracellular signalregulated kinase (ERK) activation and ERK-dependent MMP expression in monocytes 31,38) . ERK activation is known to be involved in Ang -induced AAA formation 39) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To obtain further insight into the role of incretins in the effects of DPP- activity. It has also been reported that a DPP-4I inhibited toll-like receptor 4-mediated extracellular signalregulated kinase (ERK) activation and ERK-dependent MMP expression in monocytes 31,38) . ERK activation is known to be involved in Ang -induced AAA formation 39) .…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, genetic depletion of IL-1 and the IL-1 receptor as well as pharmacological inhibition of the IL-1 receptor suppressed AAA formation in mice 30) . Ta et al reported that a DPP-4I suppressed IL-1 expression in cultured human monocytes 31) . Collectively, these results indicate that decreased IL-1 expression can in part explain the protective effect of DPP-4I against AAA formation.…”
Section: Discussionmentioning
confidence: 99%
“…DPP‐4 inhibitors are widely used antidiabetic drugs; however, the anti‐inflammatory effects against cardiovascular diseases, including myocardial infarction,16 arthrosclerosis,7, 17 and abdominal aortic aneurysms,8 have been reported in animal models. Anagliptin, a DPP‐4 inhibitor, also has anti‐inflammatory effects, and according to phase 3 clinical trials, anagliptin treatment improves serum lipid profiles 18…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vivo and in vitro studies have shown that alogliptin exerts anti-atherosclerotic effects in mice and reduces inflammation via its inhibition of monocyte activation/chemotaxis 18) . Another study also showed that alogliptin inhibited atherosclerosis in diabetic apoE-deficient mice by inhibiting the upregulation of proinflammatory cytokines by mononuclear cells 19) . Therefore, alogliptin is expected to reduce the risk of cardiovascular disease.…”
mentioning
confidence: 98%